Detection of csg and lux Genes in Biofilm-Forming Uropathogenic Escherichia coli Associated with Urinary Tract Infections - Rini Purbowati; Sri Lestari Utami; Dadik Raharjo; Masfufatun Masfufatun (Journal of Multidisciplinary Applied Natural Science, 2025)
Uropathogenic Escherichia coli (UPEC) is responsible for 80–90% of urinary tract infections (UTI) in the global population. The emergence of the increasing resistance to broad-spectrum antimicrobial agents was due to the ability to form biofilms. Cell surface factors that play a role in biofilm formation include Quorum Sensing (QS) which is encoded by the luxS family gene and curli by two operons, namely the csgBA operon. The purpose of the study is to detect the effects of 2 virulence genes (csgD and luxS) on biofilm-forming UPEC associated with UTI. As many as 76 UPEC isolates were collected from the clinical microbiology laboratories and the biofilm development was analyzed using the crystal violet method on microplate 96 wells. Using PCR assay, the two studied genes (csgD and luxS) were determined to be present in the isolates. UPEC isolates the bacteria-produced biofilms (90.80%) and nonproducers (9.20%). Most UPEC bacteria (97.36%) are known to be positive for csgD and luxS gene, while the others (92.10%) are known to be positive for the luxS gene. The highest proportion of the genes expressed in this study is followed by the presence of a relationship between the ability to produce biofilm and the presence of the genes under investigation, which is followed by all UPEC strains that cause UTI in humans.